Supplementation with lipid sources in diets for Jersey cows in the first third of lactation - Ana Paula Binato de Souza; Jorge Schafhauser Junior; Rudolf Brand Scheibler; Ana Carolina Fluck; Fábio Antunes Rizzo; José Laerte Nörnberg; Diego Prado de Vargas; Lívia Argoud Lourenço (Pesquisa Agropecuária Brasileira, 2023)
Abstract The objective of this work was to evaluate the effect of the addition of whole-crude oilseeds of linseed, sunflower, and soybean to the diet of Jersey cows, in the first third of lactation, on the following characteristics: intake, apparent nutrient digestibility, milk production and its variables, energy-corrected milk, feed efficiency, energy balance, milk fatty acid profile, and blood metabolic profile. Eight multiparous Jersey cows were used in a double Latin square design. The treatments were the experimental diets with the oilseeds, and calcium salts of fatty acids were used as the control. Protein digestibility was lower for soybean, whereas that of ether extract was higher in the control, not differing between the evaluated oilseeds. There was no difference between oilseeds for milk production, milk production corrected for fat, milk nutritional content, feed efficiency, energy balance, and blood metabolic profile. The levels of mil k monou n sat u rated fatty acids increased with the use of sunflower. Higher levels of cis-9, trans-11 conjugated linoleic acid (CLA) in milk were observed in the control. The addition of the evaluated whole-crude oilseeds to the diet of Jersey cows in the first third of lactation does not affect milk production variables, feed efficiency, energy balance, and blood biochemical profile, but alters the fatty acid profile.